Intelligent and Efficient Transport Systems Design, Modelling, Control and Simulation - Dinh, Truong Quang (2020)
The aim of this book is to present a number of digital and technology solutions to real-world problems across transportation sectors and infrastructures. Nine chapters have been well prepared and organized with the core topics as follows:-A guideline to evaluate the energy efficiency of a vehicle-A guideline to design and evaluate an electric propulsion system-Potential opportunities for intelligent transportation systems and smart cities-The importance of system control and energy-power management in transportation systems and infrastructures-Bespoke modeling tools and real-time simulation platforms for transportation system developmentThis book will be useful to a wide range of audiences: university staff and students, engineers, and business people working in relevant fields.